Pelatihan Corporate Intelligence pada Badan Pengelola Keuangan Haji di Jakarta - Ariani, Meiliyah; Zulhawati, Zulhawati; Aulawi, Dede Farhan (PARAHITA : Jurnal Pengabdian kepada Masyarakat, 2023)
Corporate Intelligence is focused on the collection and analysis of facts and other information that responds to the needs of key decision makers in the face of: major corporate action decisions that are high risk and complex and contain extraordinary risks or other important considerations required from Information collected from a variety of sources, including online information, subscriptions to highly specialized databases, hard-to-find public records,Â  and knowledgeable and experienced individuals. Analysts risk extracting key facts from the public and their subject domains to a rigorous analytical framework. This process connects various pieces of information, forming illustrations and procedures. The results support sustainable business practices by offering informed and trusted decisions in all commercial contexts. Conversely, the costs associated with violations â€“ from regulatory and legal fines to the reputation and good name of the company can be significant. The implementation of this community service activity collaborates with university lecturers Prof. Dr. Moestopo and Yogyakarta University of Technology who are also involved in the National Love Lovers Tourism Movement (GENPPARI). This training was given to personnel of the Risk Management Committee of the Hajj Financial Management Agency (BPKH) Jakarta and the results of this training were carried out to provide an understanding of the application of intelligence science in the implementation of organizational objectives as mandated by law. Starting from planning, implementing and supervising the receipt, development and expenditure of Hajj funds in order to provide the maximum benefit to Hajj pilgrims. The participants of this training were very enthusiastic because the discussion and question and answer sessions made the training atmosphere lively with various kinds of questions so that participants could ask questions related to the material presented.